2014
DOI: 10.1095/biolreprod.113.116590
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-31 is Significantly Elevated in Both Human Endometrium and Serum During the Window of Implantation: A Potential Biomarker for Optimum Receptivity1

Abstract: The window of implantation of human embryos into the endometrium spans Cycle Days 20-24 of the 28-day menstrual cycle. However, uterine receptivity may not be reliably replicated in infertile patients throughout this span. Thus, it is of importance to be able to determine optimal receptivity through a minimally invasive measure. We screened expression of a number of candidate micro-RNAs (miRNAs) in endometrial tissues and serum collected from a panel of fertile women during both the proliferative phase and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 48 publications
(48 reference statements)
0
45
0
Order By: Relevance
“…In contrast to the testes, human ovaries do not express miR‐31, although the level of miR‐31 expression was significantly elevated in both the endometrium and serum during the time of embryonic implantation (Kuokkanen et al, ; Kresowik et al, ). Uterine endometrium receptivity is critical for the success of embryo implantation (Kresowik et al, ). The exact role of miR‐31 in endometrium receptivity is not yet known; however, the observed increased miR‐31 expression during implantation suggest that it participates in the creation of an immune‐tolerant maternal environment.…”
Section: Mir‐31 Promotes Spermatogenesis and Facilitates Embryonic Immentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the testes, human ovaries do not express miR‐31, although the level of miR‐31 expression was significantly elevated in both the endometrium and serum during the time of embryonic implantation (Kuokkanen et al, ; Kresowik et al, ). Uterine endometrium receptivity is critical for the success of embryo implantation (Kresowik et al, ). The exact role of miR‐31 in endometrium receptivity is not yet known; however, the observed increased miR‐31 expression during implantation suggest that it participates in the creation of an immune‐tolerant maternal environment.…”
Section: Mir‐31 Promotes Spermatogenesis and Facilitates Embryonic Immentioning
confidence: 99%
“…CXCL12 can be directly regulated by miR‐31 in mice (Itkin et al, ). An inverse expression pattern between the levels of miR‐31 and its target FOXP3 and CXCL12 transcripts was observed in endometrium tissue and serum during the window of implantation, suggesting that miR‐31 directly suppresses FOXP3 and CXCL12 to ensure an immune‐tolerant environment for the implanted fetus (Kresowik et al, ). Thus, miR‐31 is a potential biomarker that can be used to monitor the activity of endometrium to assess the success of embryonic implantation (Kresowik et al, ).…”
Section: Mir‐31 Promotes Spermatogenesis and Facilitates Embryonic Immentioning
confidence: 99%
“…Analysis of human endometrium and trophectoderm has identified the expression of a large number of miRs ( Dior et al, 2014 , Galliano and Pellicer, 2014 , Kresowik et al, 2014 , Rosenbluth et al, 2013 ), with more recent studies demonstrating that miRs are secreted by human and bovine embryos in culture ( Kropp et al, 2014 , Rosenbluth et al, 2014 ). We hypothesised that miRs are released by human blastocysts and are taken up by endometrial surface epithelial cells to regulated endometrial receptivity and implantation.…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers believe that serum miRNAs could represent excellent non invasive molecular markers to diagnose specific diseases and also to predict response to therapy (19). Kresowik et al recently demonstrated that some miRNAs were differentially regulated in the endometrium during proliferative and secretory phases, and the expression of miR-31 was up-regulated in secretory-phase serum, identifying it as a potential biomarker for endometrial receptivity (27). Finding deregulated miRNAs in the endometrium or serum of women with CE could indicate possible changes to the physiological and well-characterized endometrial cell molecular expression pathways and this could lead to optimize specific therapies.…”
Section: Resultsmentioning
confidence: 99%